Science Learning through YouTube Channell - Muhammad Nizaar; Haifaturrahmah Haifaturrahmah; Yuni Maryati (PROCEEDING UMSURABAYA, 2020)
Abstract. Teachers‘ needs for learning media in the form of video is very important, resulting YouTube becomes one of the options in assisting students for studying. This research identifies videos of science lesson materials displayed in YouTube channel. Data in YouTube documents were analyzed using data crawling, pre-processing, and video classification based on Biology, Physics, and Chemistry group. Research samples were taken from the most favorite of five YouTube learning channels from a survey ofsaintif.com site. Research finding shows that the numbers of Biology video lesson materials are much greater compared to Physics and Chemistry lessons. Lesson material content displayed is not equally distributed yet according to the necessity of every educational level, even the lesson material tends to be the same in each channel. It requires more videos that can explain the abstract lessons those are difficult in the class